Fabry-Perot resonance enhanced electrically pumped random lasing from ZnO films - Ni, Pei Nan (2016)
Fabry-Perot (F-P) resonance has been introduced into Au/MgO/ZnO structure in order to improve the performance of electrically pumped random lasing in this structure. It is found that the lasing threshold of this structure is significantly reduced by introducing the F-P resonance due to the better optical confinement. Meanwhile, this structure shows improved random lasing output characteristics with less random lasing modes and strong dominant output mode due to the gain competition process. The results demonstrate that introducing F-P resonance into the random media provides an effective strategy towards controllable, high performance electrically pumped random lasers.